2015
DOI: 10.1586/17476348.2015.1091312
|View full text |Cite
|
Sign up to set email alerts
|

Update on the current methods for the diagnosis and treatment of severe childhood asthma

Abstract: The level of asthma control is the key outcome towards which asthma management is evaluated. The majority of children with asthma can obtain adequate control of symptoms through avoidance of triggering factors and/or with the help of low to moderate doses of current available medications. However, there is still a group of children with poor symptom control despite intensive treatment. The current review will provide an overview of a standardized approach to characterize this heterogeneous group of severely si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 103 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…60 A study by Roberts et al found children with acute life-threatening asthma requiring ventilation were much more likely to have clinical FA than those attending the emergency department with non-life-threatening exacerbations. 62 In other studies, multiple food allergies have been associated with STRA 16,60,62 It is not clear whether the observed relationship between STRA and FA is due solely to a shared stronger atopic tendency, or whether a causal pathophysiological link is responsible. 62 In other studies, multiple food allergies have been associated with STRA 16,60,62 It is not clear whether the observed relationship between STRA and FA is due solely to a shared stronger atopic tendency, or whether a causal pathophysiological link is responsible.…”
Section: Food Allergymentioning
confidence: 97%
See 4 more Smart Citations
“…60 A study by Roberts et al found children with acute life-threatening asthma requiring ventilation were much more likely to have clinical FA than those attending the emergency department with non-life-threatening exacerbations. 62 In other studies, multiple food allergies have been associated with STRA 16,60,62 It is not clear whether the observed relationship between STRA and FA is due solely to a shared stronger atopic tendency, or whether a causal pathophysiological link is responsible. 62 In other studies, multiple food allergies have been associated with STRA 16,60,62 It is not clear whether the observed relationship between STRA and FA is due solely to a shared stronger atopic tendency, or whether a causal pathophysiological link is responsible.…”
Section: Food Allergymentioning
confidence: 97%
“…61 Additionally, a study of 201 children with asthma found peanut and milk allergy were independently associated with hospitalizations for asthma exacerbations. 62 In other studies, multiple food allergies have been associated with STRA 16,60,62 It is not clear whether the observed relationship between STRA and FA is due solely to a shared stronger atopic tendency, or whether a causal pathophysiological link is responsible. 63 Several mechanisms have been proposed for a causal link.…”
Section: Food Allergymentioning
confidence: 97%
See 3 more Smart Citations